MANAJEMEN PENGELOLAAN FASILITAS OLAHRAGA PT INALUM PERSERO TAHUN 2023 - Erlangga Lubis, Zulfirman; Hasibuan, Rosmaini; Mesnan; Elvana, Ayu; Ratno, Puji; Zulaini (Fakultas Ilmu Keolahragaan Unimed, 2024)
This research aims to determine the management of PT Inalum Persero's sports facilities in 2023. This research was carried out at the PT Complex. Inalum Jalan Beringin Kota Baru Tanjung Gading, Sei-Suka District, Batu Bara Regency, North Sumatra Province. This research was conducted from April to October 2023. The research method used was a qualitative descriptive method. The sample in this study was 30 people including 3 managers or contractors, 19 employees and users of PT sports facilities. Inalum Persero 8. Data collection techniques use observation, questionnaires and interviews. The data analysis technique used by researchers in this research is quantitative and qualitative descriptive analysis. From the results of this research data analysis, it was found that the results of the planning process were 3.74 in the good category, the results of the organizing process were 3.81 in the good category, the results in the directing process were 4.50 in the very good category, and the control process was 3.91 fall into the good category. Based on the research results obtained from data analysis, it was concluded that the results of PT Inalum Persero's sports facility management planning indicators for 2023 obtained a result of 3.74 in the good category. The results of the 2023 PT Inalum Persero sports facility management organization indicators obtained a result of 3.81 in the good category. The results of PT Inalum Persero's 2023 sports facility management direction indicators obtained a result of 4.50 in the very good category. The results of the management control indicators for PT Inalum Persero's sports facility management in 2023 obtained a result of 3.91 in the good category